Peran Kepemimpinan Transformasional dan Literasi Budaya dalam Meningkatkan School Wellbeing di PAUD: Benang Emas Kesejahteraan sebagai Investasi Masa Depan Anak Usia Dini - Suryaningsih, Suryaningsih; Putra, Yudithia Dian; Sobri, Ahmad Yusuf (Kumarottama: Jurnal Pendidikan Anak Usia Dini, 2025)
The issue of school wellbeing at the Early Childhood Education (PAUD) level is the main focus in the discussion on educational leadership and strengthening cultural values, especially in the midst of social dynamics and changes in the national curriculum. This article aims to analyze the role of transformational leadership and cultural literacy in efforts to improve school welfare at the PAUD level. The hypothesis proposed states that the integration of transformational leadership and cultural literacy makes a positive contribution to the creation of a prosperous school environment. This research applies a qualitative approach with a case study design carried out at PAUD IT Insan Madani, Madiun Regency. Data collection was carried out through in-depth interviews, participatory observations, and documentation of nine informants who were selected purposively. The results of the study show that transformational leadership is able to create a work climate that supports teacher collaboration, empowerment, and innovation, while cultural literacy instills the values of local wisdom in the children's learning process. The synergy between the two strengthens the school's identity and forms sustainable welfare. This article contributes to the development of culture-based leadership models in early childhood education as a strategic approach in creating a healthy, adaptive, and meaningful educational ecosystem. These findings are important as a foothold in designing policies and leadership practices that are responsive to the local context and emotional needs of school residents